THE ANALYSIS OF THE DEVELOPMENT ALTERNATIVE ENERGY RESOURCES ON MARITIME SECTOR USING FUZZY MCDM METHODS - Sutrisno Sutrisno; Yudha Sukma Perdana; Abdul Rahman; Okol Sri Suharyo (JOURNAL ASRO, 2020)
The energy crisis has required the government to develop and utilize a renewable energy. Indonesia has a national jurisdiction area of ± 7.8 million km² with 2/3 of its territory being the sea of ± 5.9 million km². With this large sea area, it is a great potential for Indonesia to be able to develop alternative energy resources in the maritime sector amid the problem of fossil energy resources whose capacity is decreasing. Alternative energy in the maritime sector that can be developed include energy that utilizes ocean waves, ocean currents, tides, and ocean temperature differences. This study aims to determine the alternative energy of the maritime sector by reviewing from technical and financial aspects, political, economic, social and technological aspects. The method used is technical analysis, financial analysis, PEST analysis, and Fuzzy MCDM. The first step in this process is the mapping of the technical, financial, political, economic, social and technological aspects of each energy alternative with technical, financial and PEST analysis. Furthermore, with the Fuzzy MCDM method an alternative energy development selection model was made by assessing the performance of each. Based on the results of data processing shows the ranking of determining the alternative energy of the maritime sector with the first is the source of ocean current energy, the second is tidal energy, the third is wave energy and the last is Ocean Thermal Energy Conversion (OTEC). Keywords: Alternative Energy Resources, PEST, Fuzzy MCDM